Food Insecurity Moderates the Acute Effect of Subjective Socioeconomic Status on Food Consumption - Godsell, Sarah; Randle, Michael; Bateson, Melissa; Nettle, Daniel (Frontiers in Psychology, 2019)
Experimentally inducing low subjective socioeconomic status (SSES) increases food consumption in standardized eating opportunities. Separately, food insecurity (FI) has also been shown to be associated with increased opportunistic food consumption. Here, we assigned 123 adult volunteers to a low-SSES manipulation or a control condition, followed by an opportunity to consume snack foods. We measured FI prior to the experiment. Thus, our experiment served to replicate the effects of SSES and of FI on consumption, and also to establish whether these effects combine additively or interactively. The low-SSES manipulation increased food consumption, but only among participants who were food secure at baseline. Amongst food-insecure participants, the effect was reversed. This interaction was not predicted a priori and is presented as an exploratory finding. We also found evidence that both SSES and FI affected the hedonic evaluation of the snack foods. Our findings suggest that both FI and low SSES affect the consumption and evaluation of food. Their combined effects on consumption may be complex.